The effects of focus-on-form tasks on young learners' comprehension and acquisition of the simple past tense in English / Siti Khadijah Kamarulzaman - Siti Khadijah , Kamarulzaman (2018)
This study is conducted to investigate the comparative effectiveness of two Focus-on-Form (FonF) tasks namely dictogloss (DG) and consciousness-raising (C-R) on young learnersï¿½ English simple past tense. The participants were divided into three experimental groups (DG group, C-R group and control group) where they received their respective treatment. Prior to the treatment, they sat for their prettest. Immediate posttest and delayed posttest were conducted after the treatment cycles. Results of the tests have shown significant intragroup effects of dictogloss and consciousness-raising on participantsï¿½ comprehension, writing tasks and also their knowledge retention of English simple past tense over time. However, only comprehension test have shown significant intergroup (between groups) results with DG group performing better than C-R and the control groups. Interview with selected participants had also been conducted to look at the other factors that might influence these outcomes. These factors include motivation, learning styles, their affective filter and also their ï¿½noticingï¿½ awareness.